Effect of safranal on the response of cancer cells to topoisomerase I inhibitors: Does sequence matter? - Lozon, Lama; Saleh, Ekram; Menon, Varsha; Ramadan, Wafaa S.; Amin, Amr; El-Awady, Raafat (Frontiers in Pharmacology, 2022)
Lung and colorectal cancers are among the leading causes of death from cancer worldwide. While topotecan (TPT), a topoisomerase1 inhibitor, is a first- and second-line drug for lung and colon cancers, the development of drug resistance and toxicity still reserve as a major obstacle to chemotherapeutic success. Accumulating evidence indicate increased efficacy and reduced toxicity of chemotherapeutic agents upon combining them with natural products. We aim to investigate the possible interaction of safranal (SAF), a natural compound obtained from Crocus Sativus stigma, with TPT when used in different sequences in colon and lung cancer cell lines. The growth inhibitory effect of the proposed combination given in different sequences was assessed using the colony formation assay. Comet assay, cell cycle distribution, Annexin V staining and expression of proteins involved in DNA damage/repair were utilized to understand the mechanism underlying the effect of the combination. SAF enhanced the growth inhibitory effects of TPT particularly when it was added to the cells prior to TPT. This combination increased the double strand breaks induction and dysregulated the DNA repair machinery, particularly the tyrosyl- DNA phosphodiesterase1 enzyme. Additionally, SAF+TPT combination increased the fraction of cells arrested at the G2/M checkpoint as well as enhanced the induction of apoptosis. The current study highlights the status of SAF as a natural product sensitizing the lung and colon cancer cells to the cytotoxic effects of the anticancer drug TPT. In addition, it emphasizes the importance of sequence -dependant interaction which can affect the overall outcome.